Sinophone Utopias: Exploring Futures Beyond the China Dream edited by Andrea Riemenschnitter, Jessica Imbach, and Justyna Jaguscik - Spakowski, Nicola (Journal of the European Association for Chinese Studies, 2023)
Sinophone Utopias: Exploring Futures Beyond the China Dream Andrea Riemenschnitter, Jessica Imbach, and Justyna Jaguscik, eds. Amherst, New York: Cambria Press, 2023. 484 pp. ISBN: 9781621966463